Cost efficiency analysis and emission reduction by implementation of energy efficiency standards for electric motors - Mahlia, Teuku Meurah Indra; Yanti, Padli Abdul Azis (Elsevier, 2010)
The industrial sector is the biggest electricity consumer in Malaysia. Electric motors account for more than 45% of the electricity consumption in the industrial sector in the country. Therefore, it is very important to implement energy efficiency standards for electric motors to reduce energy consumption growth in this sector. This paper attempts to calculate the cost efficiency analysis and emission reduction by implementing energy efficiency standards for electric motor in Malaysia. The energy efficiency standards are proposed based on the efficiency of electric motors from survey data. The study examines the potential energy, economical and environmental impacts of the implementation of energy efficiency standards for electric motors in three scenarios i.e. 0.5%, 1.0% and 1.5% of standards efficiency improvement. Standards also enable consumers to reduce their electricity bill and contribute to a positive environmental impact. (C) 2009 Elsevier Ltd. All rights reserved.